Capturing the language of flash fiction a stylistic analysis of a Filipino-Authored "short" Short Story - Tarrayo, Veronico N. (2017)
The 21st century has witnessed the gradual popularization of flash fiction as a literary genre. However, it has not been extensively explored in literary studies, and most investigations undertaken about it were on genre studies ((Ben-Porat, 2011; Guimaraes, 2010; Lucht, 2014; Nelles, 2012; Taha, 2000) and few on its use in writing pedagogy (Batchelor & King, 2014) Lucht, 2014). In order to add to the increasing number of studies on flash fiction, this paper examines, along stylistic lines the flash fiction piece "Bettina" written by Gemino H. Abad, a renowned Filipino author. Using Leech and Short's (2007) schema, the present study attempts to decipher the language code of the said text in terms of the following features: lexical categories, grammatical categories, figures of speech, and context and cohesion. The implication of the present study for literature and language teaching are also discussed.
Keywords: Fiction; Literature